Teaching Islam - Wheeler, Brannon M., 1965- (AAR teaching religious studies., 2003)
Despite the importance of Islam in global affairs and the role of Islamic Studies in Religious Studies, little attention has been given to the basic questions of how Islam should be taught. This volume brings together a number of leading scholars of Islamic Studies with rich experience in teaching Islam in a diversity of undergraduate settings, from large public universities to small private colleges. Topics addressed include Islamic law, the Quran, Sufism, women in Islam, Islam in America, and teaching about Islam through Arabic literature and the use of new information technology. Along with.